Stop the world finding a way through the pressures of life - Watts, Murray; Cooper, Cary L. (Hodder & Stoughton, 1998)
Cooper shows that coping with stress requires a radical but positive and healing change of lifestyle and attitude. Practical advice is given for dealing with stress, including life planning, taking breaks, managing time, living in the present, meditation and diet. This is a second revised edition of "Relax: BBC Guide to Dealing with Stress"